Conjecturing Harmful Intent and Preemptive Strike in Paranoia - Horita, Yutaka (Frontiers in Psychology, 2021)
Paranoia depicts a belief of others having harmful intent. Research using economic games has exhibited the correlation between paranoia and the propensity to characterize ambiguous intentions as harmful. Using a non-clinical sample recruited online from the United States (N = 290), we examined whether paranoid thoughts influence aggressive behavior against the subjective perception of harmful intent. We conducted a preemptive strike game wherein aggressive behavior was assumed to be guided by the fear of an opponent. The outcomes indicate that 1) individuals with high paranoia assume harmful intent of an opponent more than those with low paranoia, 2) conjecturing an opponent’s harmful intent predicted an increase in the probability of a preemptive strike, 3) paranoia did not have a statistically significant effect on encouraging a preemptive strike. Additionally, the exploratory analysis revealed that paranoia was related to participant’s aggressiveness and with suppositions of other’s self-interests and competitiveness. This study presents empirical evidence that paranoia is related to perception of social threats in an uncertain situation. We discuss the possibility that paranoid ideation can promote or inhibit a preemptive strike.